Etika Komunikasi Islam pada Aktor Politik Indonesia: Kajian Wacana di Media Online - Masran (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2022)
This study aims to explore and analyze the ethical problems of communication between Indonesian political actors on social media (via news on detik.com.kompas.com, CNN.com) which indicate "violation" of norms and values ​​of Indonesian society and Islam. The perspective used is the deontological ethical theory from the West and the ethical approach to Islamic communication which is sourced from the Qur'an and hadith as well as qiyas and ijtima. The methodology implemented is CMC (computer mediated communication) to explore news and utterances that tend to have a communication ethic tendency to the three Indonesian political actors who most often have problems with public ethics. The data was obtained through texts in online media, observations of experts, and online interviews with netizens who responded to the problems of communication ethics of the political actors studied. The findings explain that political actors in Indonesia who appear on social media or are reported on online media are often not in accordance with communication ethics, especially those with Islamic principles, such as: hiwar (dialectically arguing with each other), jidal (arguing with clear sources and reaching positive agreement), tawashi (instructing each other in the truth), tabsyir (can create a happy communication space), maw'izah (compassionate love), and indzar (reminding each other to do good and right), not with a conflict approach and create disintegration.